Louis Armstrong : the soundtrack of the American experience - Stricklin, David, 1952- (Chicago : Ivan R. Dee, 2010)
Explores Louis Armstrong's life concentrating on his musical talent, identity as an African American, and the creativity and exuberance he shared with the world.
Humble origins -- A rising talent -- Hot music in a strange time -- An independent musician -- Fully free African American -- Looking to a new future -- International icon -- The soundtrack of the American experience.
Includes bibliographical references (p. 167-170) and index.
Keywords: Armstrong, Louis, -- 1901-1971.; Jazz musicians -- United States -- Biography; African American jazz musicians -- Biography